Echoventriculographic detection, localization, and quantification of left ventricular asynergy in acute myocardial infarction. A correlative echo- and electrocardiographic study. - Heikkil J (1975)
"Echoventriculography", an echocardiographic method specially developed to scan the regional function of the left ventricle, is introduced for studying left ventricular wall motion alteration in patients with acute myocardial infarction. Purposeful probe directions, a 2:1 magnification, and careful adjustment of the gain and reject levels allowed a direct echocardiographic scanning of practically the entire left ventricle. Technically acceptable echoventriculograms were obtained from the upper and lower halves of the septal, anterior, lateral, and postero-inferior left ventricle segments in all observations on 30 consecutive patients with acute myocardial infarction. Various degrees of regional left ventricular asynergy were present in 100 per cent of the patients with acute myocardial infarction. In contrast, synergic ventricular segmental wall motion was observed in 40 healthy subjects. Pronounced asynergy was already detectable within 12 hours from onset of the symptoms of acute myocardial infarction. Echoventriculography detected acute left ventricular asynergy as well in the anteroseptal or lateral as in the posteroinferior locations. The anterior and/or septal infarction (13 of the 30 patientsy always showed a paradoxical systolic motion of the, generally large, infarcted areas. The amplitude of abnormal outward motion was up to 5 mm. In the posteroinferior infarctions (17 patients) akinetic or hypokinetic modes prevailed. The contractile function of the uninvolved segments could be measured at the same time. Hypercontractile left ventricular wall motion was common in these healthy areas in acute myocardial infarction. These findings provide useful insight into the various components of the overall left ventricular pump function in acute myocardial infarction. The validity of the echoventriculographic evaluations of the segmental left ventricular function subsets was further confirmed in 2 patients undergoing left ventricular cineangiographic studies and in 2 by necropsy. The site of the asynergic left ventricular wall motion abnormalities correlated excellently with electrocardiographic prediction of the site of acute myocardial infarction. The echoventriculographic analysis proved to be more accurate in detecting asynergy than was the electrocardiogram. This new echoventriculographic method may become a useful tool for serial noninvasive alalysis of left ventricular performance, in detecting both the asynergic areas and the reserve function of the normal regions in acute myocardial infarction.